PEMANFAATAN BUAH PALA DAN BUAH LEMON DALAM PEMBUATAN MINUMAN BUBUK INSTAN - Sinaga, Dian Felicia; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Instant drink is a processed food product in powder form, easily soluble in water, practical in its presentation, and has a large surface area. The purpose of this study was to obtain the right combination of fruit and lemon meat combinations so as to produce instant drinks that meet SNI 01-4320.1996 and get consumers. The treatment in this study is P1 = nutmeg extract: lemon fruit extract (90:10), P2 = nutmeg extract: lemon fruit extract (80:20), P2 = nutmeg extract:lemon extract (80:20), P3 = nutmeg extract: lemon fruit extract (70:30), and P4 = nutmeg bark extract: lemon fruit extract (60:40). The parameters observed were water, ash , total sugar, antioxidant activity test and sensory test of aroma, color, taste, texture and overall assessment. The data obtained were statistically tested using variance. If F count is greater or equal to F table, the analysis will continue with the DNMRT test at the level of 5%. The results of variance showed that variations in the addition of lemon extract had a significant effect on water, ash, total sugar , antioxidant and descriptive sensory assessments on color parameters, aroma fineness and overall hedonic taste. The best research results of instant powder in treatment P4 (60% nutmeg bark extract ratio: 40% lemon red extract) with a moisture  of 1.72%, ash 1.29%, sugar  33.67% antioxidant 111.84 ppm, has lemon flavour, tastes lemon, and has a smooth texture and is light brown to slightly yellow in color, and overall favored by panelists. Keywords :instant powder, nutmeg, lemons